An Analysis of Figurative Language of Poetry in English Textbook for Senior High School - Faurina Anastasia; Mardatila; M. Riskiyadi Siregar (STAIN Majene, 2024)
Figurative language of poetry found in English textbook was the object of this research. This study used qualitative method and content analysis approach to identify and analyse figurative language in poetry. The data collection technique used English textbook for senior high school. Three poetry were selected as samples, identified into the types of figurative language, and then analyzed into Perrine’s theory of twelve types of figurative language. The technique analysis used the data coding to identify and analyse figurative language in the poetry. The findings of this study show that there are five types of figurative language found, namely: personification, simile, irony, metaphor, and symbol. From the five, the most used is metaphor. The significance of this research are identify and analyse the types of figurative language of poetry that presented in the English textbook used in senior high school; it can aid educators in developing targeted instructional strategies to improve students’ comprehension and appreciation of poetic devices; and the research can contribute to the evaluation and potential enhancement of the existing English textbook by providing insights into dominant types of figurative language used in the poetry content.